Workspace and Manipulability Analysis of a 4-R ̅RR Redundant Planar Parallel Manipulator - Tongtib, Amnad; Khanakornsuksan, Chawalit (RMUTL Engineering Journal, 2022)
Planar parallel manipulator has advantages to carry out high speed and accuracy tasks, but singular configurations can occur within a workspace. These singular configurations can be eliminated by adding redundant actuation. This paper presents an analysis of workspace ratio and Manipulability Index (MI) of a 4-RRR redundant planar parallel manipulator, which is created by introducing a redundant branch with active actuator to a 3-"R" ̅RR. Each branch made up as serial chain connects the moving platform to the fixed base by actuator, two rigid links and 2 passive revolute joints. A geometry method based on the forward kinematics would be appropriate to determine the workspace. Then, 4-"R" ̅RR workspace is generated by the intersection of all branched. MI of point in intersection workspace are analyzed. Finally, case study, a comparison of workspace ratio and MI of 3-"R" ̅RR and 4-"R" ̅RR parallel manipulator shown the 4-"R" ̅RR redundant structure can improve the MI to 37 times (for 400 mm and 500 mm of lower and upper link length, respectively) when compared with the 3-"R" ̅"RR" structure while the workspace ratio reduced to 13.15%.